1998
DOI: 10.1128/jb.180.9.2280-2284.1998
|View full text |Cite
|
Sign up to set email alerts
|

Metalloadsorption by Escherichia coli Cells Displaying Yeast and Mammalian Metallothioneins Anchored to the Outer Membrane Protein LamB

Abstract: Yeast (CUP1) and mammalian (HMT-1A) metallothioneins (MTs) have been efficiently expressed in Escherichia coli as fusions to the outer membrane protein LamB. A 65-amino-acid sequence from the CUP1 protein of Saccharomyces cerevisiae (yeast [Y] MT) was genetically inserted in permissive site 153 of the LamB sequence, which faces the outer medium. A second LamB fusion at position 153 was created with 66 amino acids recruited from the form of human (H) MT that is predominant in the adipose tissue, HMT-1A. Both La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(47 citation statements)
references
References 46 publications
(53 reference statements)
3
42
1
1
Order By: Relevance
“…Enhanced Cd 2+ accumulation by genetically engineered E. coli with surface-expressed metal-binding peptides have been reported by others (Sousa et al, 1996(Sousa et al, , 1998Xu and Lee, 1999). One of the most successful is the LamB fusion system, which has been used to anchor MTs and short metal-binding peptides onto the surface of E. coli (Kotrba et al, 1999;Sousa et al, 1998). However, the Cd 2+ binding capability of cells expressing EC20 is almost twice the amount obtained using the LamB system .…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced Cd 2+ accumulation by genetically engineered E. coli with surface-expressed metal-binding peptides have been reported by others (Sousa et al, 1996(Sousa et al, , 1998Xu and Lee, 1999). One of the most successful is the LamB fusion system, which has been used to anchor MTs and short metal-binding peptides onto the surface of E. coli (Kotrba et al, 1999;Sousa et al, 1998). However, the Cd 2+ binding capability of cells expressing EC20 is almost twice the amount obtained using the LamB system .…”
Section: Discussionmentioning
confidence: 98%
“…Attempts to develop useful biosorbents by increasing the heavy metal content of plants, algae or microorganism via genetic engineering have been made in recent years (Ma et al, 2001;Maitani et al, 1996;Sar and D'Souza, 2001). Although significant improvements in heavy metal accumulation have been observed (Li et al, 2000;Pazirandeh et al, 1995) by the overexpression of metal-chelating peptides such as metallothioneins (Sousa et al, 1998) or synthetic phytochelatins (Bae et al, 2000(Bae et al, , 2001, the ability of these peptides in arsenite binding has never been confirmed. Naturally occurring phytochelatins are particularly attractive alternatives as they are not subject to extensive proteolysis because of the g-carboxyamide bond between Glu and Cys, and they are known to bind to arsenic with high affinity (Sauge-Merle et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Bioremediation using microbes is often considered as a cost effective and efficient way of removing heavy metals (Mejare and Bulow, 2001). Several attempts have been made to enhance the intracellular heavy metal content of microorganisms by expressing metal-chelating peptides such as metallothioneins (MT) (Ma et al, 2001;Sar and D'Souza, 2001;Say et al, 2003;Sousa et al, 1996Sousa et al, , 1998, however, they generally lacked specificity and affinity for As. Recently, it was shown that specific arsenic accumulation in E. coli can be achieved by expressing an arsenic-binding protein arsR (Kostal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on surface display of yeast and mammalian MTs in recombinant E. coli cells [148150]. Sousa et al [149] reported on a 15–20‐fold increase in Cd accumulation for E. coli cells displaying yeast (CUP1) and mammalian (HMT‐1A) MTs anchored to the OMP LamB, and similar reports have been published by others [148,150]. The use of laboratory strains of E. coli might, however, not be suitable for in situ soil remediation and other more suitable strains have therefore been investigated [31,54].…”
Section: Applications For Bacterial Surface Displaymentioning
confidence: 99%